When Unity Is Strength: The Strategies Used by Chlamydomonas to Survive Environmental Stresses - Félix de Carpentier; Stéphane D. Lemaire; Antoine Danon (Cells, 2019)
The unicellular green alga Chlamydomonas reinhardtii is a valuable model system to study a wide spectrum of scientific fields, including responses to environmental conditions. Most studies are performed under optimal growth conditions or under mild stress. However, when environmental conditions become harsher, the behavior of this unicellular alga is less well known. In this review we will show that despite being a unicellular organism, Chlamydomonas can survive very severe environmental conditions. To do so, and depending on the intensity of the stress, the strategies used by Chlamydomonas can range from acclimation to the formation of multicellular structures, or involve programmed cell death.